Pentingnya Pengetahuan: Menyelidiki Pengaruh Literasi Keuangan terhadap Perilaku Keuangan di Kalangan Gen Z - Mu'afi, Muhammad Irfan; Afifah, Difansya Arkannisa; Binantara, Axelliano Dinovan (Jurnal Paradigma, 2024)
Gen Z faces difficulties in managing finances wisely, such as difficulties in making ends meet from the income they have and worries about their ability to meet their expenses. Gen Z's financial behavior is associated with changes in consumption patterns that are influenced by technological advances and the rapid development of the times. This factor is often accompanied by a lack of social responsibility and a lack of financial planning, including saving, investing, planning emergency funds, and allocating funds for the future. The purpose of this study was to determine the effect of Financial Literacy on Financial Behavior in UPN Veteran Yogyakarta students. The population used in this study were UPN Veterans Yogyakarta students and the sampling technique used was a purposive sampling technique because it requires certain criteria to answer research problems with the sample criteria being active students from Yogyakarta National Development University, class of 2019-2022 whose average age is 18 -20 years. The samples taken were 250 respondents. In this study it was concluded that financial literacy has a significant positive effect on financial behavior. The better one's level of financial literacy, the better one's financial behavior will be.